Unit vector template generator applied to a new control algorithm for an UPQC with instantaneous power tensor formulation, a simulation case study - Yeison Alberto Garcés Gómez; Nicolás Toro García; Fredy Edimer Hoyos (Institute of Advanced Engineering and Science, 2020)
In this paper we present a new algorithm to generate the reference signals to control the series and parallel power inverters in an unified power quality conditioner “UPQC” to enhance power quality. The algorithm is based in the instantaneous power tensor formulation which it is obtained by the dyadic product between the instantaneous vectors of voltage and current in n-phase systems. The perfect harmonic cancelation algorithm “PHC” to estimate the current reference in a shunt active power filter was modified to make it hardy to voltage sags through unit vector template generation “UVGT” while from the same algorithm it extracts the voltage reference for series active power filter. The model was validated by mean of simulations in Matlab-Simulink®.